Prolonged stimulation with low-intensity ultrasound induces delayed increases in spontaneous hippocampal culture spiking activity - Kim, Hyun-Bum; Swanberg, Kelley M.; Han, Hee-Sok; Kim, Jung-Chae; Kim, Jun-Woo; Lee, Sungon; Lee, C. Justin; Maeng, Sungho; Kim, Tae-Seong; Park, Ji-Ho (John Wiley & Sons Inc., 2017)
Ultrasound is a promising neural stimulation modality, but an incomplete understanding of its range and mechanism of effect limits its therapeutic application. We investigated the modulation of spontaneous hippocampal spike activity by ultrasound at a lower acoustic intensity and longer time scale than has been previously attempted, hypothesizing that spiking would change conditionally upon the availability of glutamate receptors. Using a 60-channel multielectrode array (MEA), we measured spontaneous spiking across organotypic rat hippocampal slice cultures (N=28) for 3min each before, during, and after stimulation with low-intensity unfocused pulsed or sham ultrasound (spatial-peak pulse average intensity 780W/cm(2)) preperfused with artificial cerebrospinal fluid, 300M kynurenic acid (KA), or 0.5M tetrodotoxin (TTX) at 3ml/min. Spike rates were normalized and compared across stimulation type and period, subregion, threshold level, and/or perfusion condition using repeated-measures ANOVA and generalized linear mixed models. Normalized 3-min spike counts for large but not midsized, small, or total spikes increased after but not during ultrasound relative to sham stimulation. This result was recapitulated in subregions CA1 and dentate gyrus and replicated in a separate experiment for all spike size groups in slices pretreated with aCSF but not KA or TTX. Increases in normalized 18-sec total, midsized, and large spike counts peaked predominantly 1.5min following ultrasound stimulation. Our low-intensity ultrasound setup exerted delayed glutamate receptor-dependent, amplitude- and possibly region-specific influences on spontaneous spike rates across the hippocampus, expanding the range of known parameters at which ultrasound may be used for neural activity modulation. (c) 2016 Wiley Periodicals, Inc.